Estimation of episodic groundwater recharge in semi-arid fractured hard rock aquifers - Van Wyk, Ettienne (University of the Free State, 2010)
The semi-arid regions of southern Africa cover large portions of settled land where domestic and agricultural activities depends on isolated groundwater systems replenished by irregularly occurring rainfall events. Southern African rainfall patterns are regulated by the annual oscillation of winter-summer weather systems and most of all, abrupt changes in regional atmospheric patterns, which may result in either wet/dry cycles. Given the highly differential hydro-climatic conditions and hydrogeological environment in semi-arid regions, effective groundwater recharge events are episodic in nature and largely occur once in every five years. Sustainable, medium-term management of local groundwater resources requires dynamic hydrological information to ensure a healthy supply-demand balance; thus requiring dedicated hydrological monitoring. High-level monitoring programmes on a few experimental sites have produced localised hydrological data, which illustrate how erratic groundwater resources are replenished. For many years, it was postulated that groundwater resources were recharged every time the total annual rainfall peaks a certain threshold. This postulation may hold in humid regions, but surely not elsewhere in the drier parts of South Africa. Semi-arid regions portray a flattish regional landscape with occasionally elevated parent rock windows and mountainous regions. Soil cover is restricted to low-relief areas, and lacks the thick mature soils distinctive of the humid areas. Fractured hard rock windows with very little soil cover represent potential groundwater recharge terrains, allowing recharge-producing surplus rainfall to infiltrate directly into the underlying aquifer. The hydrogeological conditions of hard rock terrains in the same-arid environment do vary in terms of the rock types and their response on weathering processes. Nonetheless, an array of joints and fractures running from ground surface into the SZ represents fast and effective pathways when episodic high rainfall events occur. Mature soil/regolith profiles in plain areas enhances surface run-off and support local floods in rivulets where riparian vegetation and open-water evaporation intercepts most of the available bank storage and depression recharge. Atmospheric moisture is, in principal, generated by warm, evaporating maritime waters, and is therefore marked by its hydrochemical signature. This signature changed abruptly during its continental migration, and finally manifests as cloud water. Winter rainwater specifically demonstrates the impact of oceanic aerosols, hence characterized by a prominent NaCl composition. Summer rainwater is a diluted version due to continental rainfall/evapotranspiration events, and is transformed by anthropogenic airborne substances peaking during the late-winter months. The hydrogeochemical composition of rainwater is therefore quite diverse, and needs logic monitoring to understand its seasonal cyclic oscillation. Short-term hyetograph observations report episodic rainfall events, occurring mostly over the January-March period of wet hydrological cycles. These are spaced over a period of 4 to 8 days, of which at least one rain event exceeds ~45 mm, associated with a rain-rate intensity of >1.5 mm·h-1. Extraordinary depleted rainwater hydrochemistry and isotopic compositions are associated with these rain weeks, which are significantly different from normal seasonal concentrations. Wet Cl− concentrations during these high rainfall periods are almost an order of magnitude lower than the average annual values. Hyetograph-hydrograph sets confirm that extraordinary groundwater recharge occurs as the result of episodic rainfall events. Hydrogeochemical profiling in the upper section of the unsaturated zone verify the presence of different compositions which probably indicate different modes of recharged rainwater percolation in fractured, hard rock terrains. Hard rock profile sections below the rebound water table interface containing almost 50% less Cl− than country-wide background values of ~40 mg·H-1. Isotopic compositions in a typical rain week period report similar depleted concentrations and resemble a prominent amount effect. Such depleted rainwater is merely linked to specific seasons, for example the rainfalls of 2003-2004, 2005-2006 and 2007-2008 hydrological years can be clustered as high rainwater input periods with notable lighter isotopic compositions; around - 7.5‰ M18O, -41‰ M2H. The fact that most of the two (2) meter vertical profiles reported relatively negative isotopic compositions (-8‰ M18O, -44‰ M2H), indicates a high probability of preferential recharge with pristine rainwater with even more negative isotopic composition. Direct groundwater recharge estimations from local, short-term rainfall and groundwater rebound stage hydrochemical data proposes a recharge value <2% in most flat lying, semi-arid regions. Although fractured hard rock terrains are isolated, it allows in the order of 4%, where as local mountainous areas are high at 14%; obviously enhanced by orographic rainfall development. Recharge on dolomitic terrains are highly variable due to diverse ground surface conditions, and may vary between 6% in flat lying plains to 13% in mountainous regions (Kuruman Hills at Kuruman). Groundwater recharge varies significantly spatially. The control by prominent soil/regolith cappings is that high that establishing realistic recharge figures for a particular area, will require a dedicated soil mapping programme to identify direct recharge terrains.
Thesis (Ph.D. (Geohydrology))--University of the Free State, 2010
Keywords: Hydrologic models -- Africa, Southern; Aquifer storage recovery; Groundwater recharge -- Arid regions; Arid regions -- Africa, Southern